Literary studies as an intersection of apologia and invective: translation decisions in the first complete rendition of the Roman poet Catullus in Bulgarian (Philology, 2019)
This paper reflects on some characteristics of the first complete translation of Catullus’ poetry book in Bulgarian, which was published in 1996. As literature and poetic writing denote a central topic in Catullus' poetry, it often becomes a point of intersection for the defense of neoteric poetry and polemics with the poet’s opponents and untalented or clumsy writers, which is reflected in the idiom used.The analysis is based on several keywords extracted from Catullus’ defensive and invective lexical register and foregrounds some important shifts in the Bulgarian translation. These shifts result in the destruction of the paramount relational structures underlying the surface textual level and in the alteration and deformation of the poet’s argumentative logic. Most significantly, they engender a substantial change in the poet’s figure as an advocate of his own poetics and the poetics of his literary circle, and as an antagonist to their critics
Keywords: Latin poetry; Catullus; Bulgarian translation